The Degree Represent of the Faculty Members in Official Jordanian Universities for the Human Relation Amongst them (University Collegiality) as a Professional Ethical Behavior - Abu Al-Nadi, Maram Fuad (Modern applied science, 2018)
This study aims at identifying the degree represent of the faculty members in official Jordanian Universities for the human relation among them (University Collegiality) as a professional ethical behavior, the survey methodology has been used in this study, and developed questionnaire consists of (26) paragraphs, and the tool has been verified its validity and reliability. The study sample consisted of official Jordanian universities’ members represented by the universities of Jordan, Yarmouk and Mutah, a total of (300) member, were selected in a simple random method, and the study concluded the following results:The Arithmetical averages and standard deviations showed that the degree of represent the faculty members in official Jordanian Universities for the human relation among them (University Collegiality) as a professional ethical behavior it was a medium degree.The result showed statistically significant differences at the significance level (p=0.05) in the estimates of the study sample members for the degree represent of the faculty members in official Jordanian Universities for the human relation among them (University Collegiality) as a professional ethical behavior, it referred to gender variable, and it was in favor of males, the results also showed statistically significant differences for the faculty class and it was in favor of sciences faculties, also showed statistically significant differences for the academic rank and it was in favor of associate Professor rank.The study recommended to focus on the subject of the University Collegiality among the faculty members and develop an agreement of the university collegiality in participation of official and unofficial Jordanian universities.